Green Human Resource Management and its Role in Enhancing Organizational Excellence : An Analytical Study at the Northern Technical University / Mosul: Manajemen Sumber Daya Manusia Berwawasan Lingkungan dan Perannya dalam Meningkatkan Keunggulan Organisasi: Sebuah Studi Analitis di Universitas Teknik Utara / Mosul - Dr. Saja Nather HamidAl-Sarraf Al-Sarraf (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Organizations increasingly adopt environmentally oriented human resource practices to support sustainability goals and long-term competitiveness. Specific Background: Green human resource management integrates environmental principles into HR functions to encourage pro-environmental behavior and organizational development. Knowledge Gap: Despite growing interest, limited studies examine its linkage with organizational brilliance within specific institutional contexts. Aims: This study aims to analyze the role of green human resource management in shaping organizational brilliance through relevant organizational mechanisms. Results: The findings indicate that green HR practices are associated with improved organizational processes and employee engagement, contributing to higher levels of organizational brilliance. Novelty: The study offers an integrated perspective by linking green HRM practices with organizational brilliance within a unified analytical framework. Implications: These results highlight the importance of adopting structured green HR strategies to support sustainable organizational development and managerial decision-making Keyword: Green Human Resource Management, Organizational Brilliance, Sustainability Practices, Employee Behavior, Organizational Development Key Findings Highlights Environmentally oriented HR practices support internal organizational alignment Employee engagement patterns reflect sustainability-oriented management approaches Integrated frameworks provide clearer understanding of organizational performance dynamics